DETERMINANTS THE INTEGRITY OF FINANCIAL STATEMENTS WITH WHISTLEBLOWING SYSTEM AS THE MODERATING VARIABLE - Asfeni Nurullah; Nur Khamisah; Nilam Kesuma (AKUNTABILITAS, 2022)
This research is a comparative causal research which is a research design to examines changes in one variable due to another variable with a causal relationship pattern. The type of data used in this study is secondary data that comes from other sources and has been processed by other researchers. Secondary data is sourced from the annual reports of financial companies for 2018-2020 period which can be accessed on the official website of the Indonesia Stock Exchange or each financial sector company. The results of the study found that Internal Audit, Company Size, and Leverage had a significant effect on the integrity of the company's financial statements, while the audit committee had no significant effect. It was also found that the existence of a whistleblowing system will strengthen the influence between each independent variable on the integrity of the financial statements..